The International Conference on Operations Research: A Report - Hertz, David Bendel (Management Science, 1958)
The Institute of Management Sciences joined with the Operations Research Society of America, and with The Operational Research Society of the United Kingdom, to co-sponsor an International Conference on Operations Research. This is a report about this conference.